Enhanced Energetic Performances Based on Integration with the Al/PTFE Nanolaminates - Yuxin Zhang; Yichao Yan; Yao Wang; Mengting Ai; Hongchuan Jiang; Liang Wang; Xiaohui Zhao; Wanli Zhang; Yanrong Li (Nanoscale Research Letters, 2018)
Abstract Integrating energetic materials on a chip has received great attention for its widely potential applications in the microscale energy consumption system, including electric initiation device. In this article, reactive Al/PTFE nanolaminates with periodic layer structure are prepared by magnetron sputtering, which consists of fuel Al, oxidant PTFE, and inert layer Al-F compound in a metastable system. The as-deposited Al/PTFE nanolaminates exhibit a significantly high energy output, and the onset temperature and the heat of reaction are 410 °C and 3034 J/g, respectively. Based on these properties, an integrated film bridge is designed and fabricated via integrating Al/PTFE nanolaminates with a Cu exploding foil, which exhibits enhanced energetic performances with more violent explosion phenomenon, larger quantities of ejected product, and higher plasma temperature in comparison with the Cu film bridge. The kinetic energy of flyers derived from the expansion of the Cu film bridge is also increased around 29.9% via integration with the Al/PTFE nanolaminates. Overall, the energetic performances can be improved substantially through a combination of the chemical reaction of Al/PTFE nanolaminates with the electric explosion of the Cu film bridge.